GLOBAL HEGEMONY VS. REGIONAL HEGEMONY: HOW THE US STRATEGICALLY INFLUENCES POWER - M. Crosston (Сравнительная политика, 2020)
The article explores the controversial thesis that the United States strategically and consistently maneuvers against the emergence of regional hegemons across the globe. Whether it is Russia in the former Soviet space, China across the South China Sea, the United States works to disallow the expression of regional hegemonic power despite its own continued reliance on its global hegemony being accepted. The author goes to the heart of power positioning and exploitation in the 21st century: is the emergence of regional hegemons disruptive to the global system or benefi cial? Is the United States’ concerns altruistic or selfi shly motivated by its own national security interests and global infl uence? Does it matter who is trying to wield regional infl uence? These and other questions are addressed, providing a new approach to understanding how power is being wielded today and for the foreseeable future.